JC Virus PCR Detection Is Not Infallible: A Fulminant Case of Progressive Multifocal Leukoencephalopathy with False-Negative Cerebrospinal Fluid Studies despite Progressive Clinical Course and Radiological Findings - Mohamed-Ali Babi; William Pendlebury; Steven Braff; Waqar Waheed (Case Reports in Neurological Medicine)
We describe a case with a false-negative PCR-based analysis for JC virus in cerebrospinal fluid (CSF) in a patient with clinical and radiological findings suggestive of progressive multifocal leukoencephalopathy (PML) who was on chronic immunosuppressive therapy for rheumatoid arthritis. Our patient developed rapidly progressive global decline with clinical and radiographic findings suggestive of PML, but JC virus PCR in CSF was negative. The patient passed away 3 months from the onset of her neurological symptoms. Autopsy confirmed the diagnosis of PML with presence of JC-polyoma virus by immunohistochemical staining. This case highlights the potential of false-negative JC virus PCR in CSF when radiographic and clinical features are suggestive of “possible PML.” We review the plausible causes of potential false-negative CSF results and suggest that when the clinical presentation is suspicious for PML repeat CSF analysis utilizing ultrasensitive PCR assay and subsequent brain biopsy should be considered if CSF remains negative. Additionally, appropriate exclusion of other neurologic conditions is essential.